Emotion, Affect and Personality in Speech The Bias of Language and Paralanguage - Johar, Swati; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book explores the various categories of speech variation and works to draw a line between linguistic and paralinguistic phenomenon of speech. Paralinguistic contrast is crucial to human speech but has proven to be one of the most difficult tasks in speech systems. In the quest for solutions to speech technology and sciences, this book narrows down the gap between speech technologists and phoneticians and emphasizes the imperative efforts required to accomplish the goal of paralinguistic control in speech technology applications and the acute need for a multidisciplinary categorization system. This interdisciplinary work on paralanguage will not only serve as a source of information but also a theoretical model for linguists, sociologists, psychologists, phoneticians and speech researchers.
Introduction -- Psychology of Voice -- Language, Communication and Human Behaviour -- Multimodality and Spoken Dialogue Systems -- Emotional Speech Recognition -- Where Speech Recognition is Going: Conclusion and Future Scope.
Keywords: Signal processing; Computational linguistics; User interfaces (Computer systems).; Human-computer interaction; Signal, Speech and Image Processing; Computational Linguistics; User Interfaces and Human Computer Interaction